Community pathways for the early detection and risk stratification of chronic liver disease: a narrative systematic review. (August 2022) - Abeysekera, Kushala W M; Macpherson, Iain; Glyn-Owen, Kate; McPherson, Stuart; Parker, Richard; Harris, Rebecca; Yeoman, Andrew; Rowe, Ian A; Dillon, John F
Summary: Patients with chronic liver disease are often diagnosed during an index presentation to hospital with decompensated cirrhosis or liver-related events, and these presentations are associated with high mortality. However, there is often a long asymptomatic phase, in which there is an opportunity for earlier diagnosis and interventions to prevent progression to advanced disease. Therefore, strategies for early diagnosis and interventions (including behavioural changes and pharmacological treatments) that prevent patients progressing to cirrhosis and its associated complications probably have substantial benefits for patients and health-care services. Many community pathways have been generated. Some pathways focus on abnormal liver function tests as a starting point to diagnose liver disease. Other pathways target groups at greater risk of chronic liver disease—particularly people with harmful alcohol consumption, type 2 diabetes, and obesity. This systematic review summarises the existing strategies available for the early detection or risk stratification of liver disease, focusing primarily on alcohol-related liver disease and non-alcoholic fatty liver disease. Conducting randomised clinical trials that compare different strategies will be essential to elucidate which pathways are acceptable to patients, feasible, provide high diagnostic accuracy for the detection of liver disease, improve liver-related outcomes, and are most cost-effective at the population level.